Integer wavelet transform‐based secret image sharing using rook polynomial and hamming code with authentication - Sara Charoghchi; Zahra Saeidi; Samaneh Mashhadi (CAAI Transactions on Intelligence Technology)
Abstract As an effective way to securely transfer secret images, secret image sharing (SIS) has been a noteworthy area of research. Basically in a SIS scheme, a secret image is shared via shadows and could be reconstructed by having the required number of them. A major downside of this method is its noise‐like shadows, which draw the malicious users' attention. In order to overcome this problem, SIS schemes with meaningful shadows are introduced in which the shadows are first hidden in innocent‐looking cover images and then shared. In most of these schemes, the cover image cannot be recovered without distortion, which makes them useless in case of utilising critical cover images such as military or medical images. Also, embedding the secret data in Least significant bits of the cover image, in many of these schemes, makes them very fragile to steganlysis. A reversible IWT‐based SIS scheme using Rook polynomial and Hamming code with authentication is proposed. In order to make the scheme robust to steganalysis, the shadow image is embedded in coefficients of Integer wavelet transform of the cover image. Using Rook polynomial makes the scheme more secure and moreover makes authentication very easy and with no need to share private key to participants. Also, utilising Hamming code lets us embed data with much less required modifications on the cover image which results in high‐quality stego images.